On the Overlap Between Everything and Nothing - Carrara, Massimiliano; Mancini, Filippo; Smid, Jeroen (Logic and Logical Philosophy, 2021)
Graham Priest has recently proposed a solution to the problem of the One and the Many which involves inconsistent objects and a non-transitive identity relation. We show that his solution entails either that the object everything is identical with the object nothing or that they are mutual parts; depending on whether Priest goes for an extensional or a non-extensional mereology.